An active frequency drift method for island problem of grid‐connected photovoltaic power generation system. Issue 11 (28th July 2019) - Xu, Ji; Zhou, Hong; Fang, Yanjun
Abstract : Island problem in grid‐connected photovoltaic power generation system has a large influence on the safety and reliability of system, which needs to be timely detected. In this article, the photovoltaic grid‐connected generation and island problems were briefly introduced, and then active frequency drift (AFD) method for island detection was studied. It was found that AFD might affect the quality of output current. Therefore, an improved AFD method was proposed, which added a phase shift change to the original reference current. The simulation experiment suggested that the improved AFD method proposed in this article could detect the islanding problem in 0.1 s, and the total harmonic distortion of the output current was 1.62%, much less than that of the AFD method. The experimental results show that the improved AFD method has better performance in island detection, with high security and reliability, and is worth popularizing widely in photovoltaic grid‐connected power generation systems. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.